Elements of Grammatical Ppreference for Morphological Construction: Model construction and Application in Usage Patterns Characterized by Lack in Alkitab by Sibawayh - Al-Khrissat, Mohammad Ahmad Hwaimel (Dirasat: Human and Social Sciences, 2024)
Objectives: The study seeks to identify the elements through which the morphological construction rules are verified, and to reveal the relationship between their availability in the usage patterns and the acceptability by language users. Its aim is to build an analytical model that reveals the grammatical quality of morphological usage patterns, and to demonstrate its tools that enable researchers to employ it in analyzing and comparing morphological usage patterns. Method: The study used the descriptive and analytical approach. As for the description, it is based on an extrapolation of the attitudes of Arabic scholars and contemporary researchers regarding the tools by which the grammaticality of the morphological usage pattern is verified and its ability to be taken as a criterion for comparison between the patterns used for the function of the structure itself. As for the analysis, it is based on a review of a set of usage patterns marked in Sibawayh’s book as “a few”, to reveal the usability of the proposed model for analysis, and to find out the motives that made linguistic practice refrain from it. Results: The study has reached a number of results, such as verifying the grammaticality of the morphological usage pattern through four elements: lightness, similarity, unambiguity, and semantics. Whenever these elements meet in a pattern of use, it is acceptable, common in use, and reliable in analogy. The more the usage pattern lacks all or some of them, the less acceptable it is to use, and the space for its spread in linguistic practice is limited. The lack of use of the linguistic pattern is an indication of a problem related to the availability and verification of the elements of grammatical preference. Conclusion: The study recommends that the elements of grammatical preference constitute a measure that depicts the conditions of usability acceptability. If the first is built by grammarians, the second is mentally present in the users’ linguistic system and has been reflected in their choices.